Investigation of continuous wave and pulsed laser performance based on Nd3+:Gd0.6Y1.4SiO5 crystal. (18th November 2015) - Feng, Chao; Liu, Zhaojun; Cong, Zhenhua; Shen, Hongbin; Li, Yongfu; Wang, Qingpu; Fang, Jiaxiong; Xu, Xiaodong; Xu, Jun; Zhang, Xingyu
Abstract: We systematically investigated a laser diode (LD) pumped Nd:GYSO (Nd 3+ :Gd0.6 Y1.4 SiO5 ) laser. The output power of the continuous wave laser was as high as 3.5 W with a slope efficiency of 31.8%. In the Q-switched operation; the laser exhibited dual-wavelengths output (1073.6 nm and 1074.7 nm) synchronously with a Cr 4+ :YAG as the saturable absorber (SA). Additionally, a passively mode-locked laser was demonstrated using a semiconductor SA mirror with a maximum average output power of 510 mW at a central wavelength of 1074 nm, while the pulse width of the laser was as short as 5 ps. Our experiment proved that the Nd:GYSO mixed crystal was a promising material for a solid-state laser.